2022
DOI: 10.1177/00258172221111919
|View full text |Cite
|
Sign up to set email alerts
|

Lovers and killers: A forensic medical study of female intimate partner homicide in the Republic of Ireland

Abstract: Female intimate partner homicide (FIPH) is an increasingly complex and significant issue globally. It is rapidly becoming a politically heavy subject for the Irish government, and a continuing and concerning problem for the criminal justice system. Recent years have seen a substantial increase in the unlawful killings of women by their husbands, current and ex-partners. In a review of 117 cases of FIPHs over a 30-year period, 1991–2021, examining the age of both victims and perpetrators, causes of death, motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…But other factors such as alcohol, drug addition, financial pressures and mental illness were also present but in lesser numbers. 17 Mental illness had a significant role in cases; however, it was not as prevalent in IPHs with only nine cases of which five were chronic in nature. In comparison with family members, it was the primary motive in 17 out of 20 cases of matricides.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…But other factors such as alcohol, drug addition, financial pressures and mental illness were also present but in lesser numbers. 17 Mental illness had a significant role in cases; however, it was not as prevalent in IPHs with only nine cases of which five were chronic in nature. In comparison with family members, it was the primary motive in 17 out of 20 cases of matricides.…”
Section: Discussionmentioning
confidence: 94%
“…The homicides tended to occur at weekends between individuals known to each other often following an argument. 16 A recent study on 116 IPHs found the leading causes of death were stabbing, strangulation, blunt force trauma and gunshot injuries with the majority of killings committed by husbands and boyfriends, 17 and the leading motive was jealousy and estrangement.…”
Section: Homicide In Irelandmentioning
confidence: 99%
“…Most female victims are killed by intimate partners or family members. A controlling attitude and possessiveness often characterize the alleged offender in these cases, as well as the fear of the victim leaving the relationship when the perpetrator is an intimate partner 4,5 . However, it can also occur in other contexts, such as rape, sexual violence, harmful practices, hate crimes, and organized crime, making it harder to keep track of the actual number of cases.…”
mentioning
confidence: 99%
“…A controlling attitude and possessiveness often characterize the alleged offender in these cases, as well as the fear of the victim leaving the relationship when the perpetrator is an intimate partner. 4,5 However, it can also occur in other contexts, such as rape, sexual violence, harmful practices, hate crimes, and organized crime, making it harder to keep track of the actual number of cases. Violence against women is affected by extremely heterogeneous geographical variability: in some countries, rape homicide prevalence is even higher than that of all female homicides in the United States, whereas other areas suffer from a growing number of female victims of urban violence and organized crime.…”
mentioning
confidence: 99%